Optical Limiting and Femtosecond Pump-Probe Transient Absorbance Properties of a 3,5-distyrylBODIPY Dye - Ngoy, Bokolombe P.; May, Aviwe K.; Mack, John; Nyokong, Tebello (Frontiers in Chemistry, 2019)
The optical limiting (OL) properties of a 3,5-di-p-benzyloxystyrylBODIPY dye with an p-acetamidophenyl moiety at the meso-position have been investigated by using the open-aperture Z-scan technique at 532 nm with 10 ns laser pulses. There is a ca. 140 nm red shift of the main spectral band to 644 nm relative to the corresponding BODIPY core dye, due to the incorporation of p-benzyloxystyryl groups at the 3,5-positions. As a result, there is relatively weak absorbance across most of the visible region under ambient light conditions. Analysis of the observed reverse saturable absorbance (RSA) profiles demonstrates that the dye is potentially suitable for use in optical limiting applications as has been reported previously for other 3,5-distyrylBODIPY dyes. Time-resolved transient absorption spectroscopy and kinetic studies with femtosecond and nanosecond scale laser pulses provide the first direct spectral evidence that excited state absorption (ESA) from the S1 state is responsible for the observed OL properties.